MODEL KINETIKA KEKERASAN GULA CETAK TEBU DENGAN PENAMBAHAN BUBUK KAYU MANIS SELAMA PENYIMPANAN - Sari, Cindy Fatika; Khairani, Lisma; Fauziah, Rahmi; Andasuryani (Prodi Teknologi Pangan Fakultas Pertanian Universitas Islam Indragiri, 2023)
The sugar cane juice produced through evaporation is processed into molded cane sugar. Adding cinnamon powder to cane sugar provides additional benefits for body health. One of the quality criteria for molded cane sugar is its hardness. The hardness value of printed cane sugar changes during storage; the sugar becomes softer and less complicated. Reaction kinetics can be used to observe changes in the hardness of printed cane sugar. The Arrhenius method was used in this research to determine how adding cinnamon powder affects the quality of molded cane sugar. This research used molded cane sugar with two concentrations of cinnamon powder, namely 0% and 0.255%. The sugar was then stored at three different temperatures, seven °C, 27 °C, and 45 °C, over 30 days, with daily observations. Kinetic analysis of molded cane sugar shows that when cinnamon powder is added, the quality decreases more quickly compared to control molded cane sugar, which has a k value of 0.3378 N/cm2/day at a temperature of 7°C, 0.4629 N/cm2/day at a temperature of 27°C, and 2.2728 N/cm2/day at a temperature of 27°C. Compared with storage temperatures of 27°C and 45°C, a temperature of 7°C showed a slower decline in the quality of molded cane sugar.